Donor Troponin and Survival After Cardiac Transplantation: An Analysis of the United Network of Organ Sharing Registry. (June 2016) - Madan, Shivank; Saeed, Omar; Shin, Jooyoung; Sims, Daniel; Goldstein, Daniel; Piña, Ileana; Jorde, Ulrich; Patel, Snehal R.
Abstract : Background—: Despite a limited supply of organs, only 1 in 3 potential donor hearts is accepted for transplantation. Elevated donor troponin levels have generally been considered a contraindication to heart transplantation; however, the data supporting this practice are limited. Methods and Results—: We identified 10 943 adult (≥18 years) heart transplant recipients in the United Network of Organ Sharing (UNOS) database with preserved donor left ventricular ejection fraction (≥50%) and where peak donor troponin I values were available. When analyzed as a continuous variable, there was no association between peak donor troponin levels and recipient mortality up to 1 year follow-up in unadjusted (hazards ratio, 0.999; 95% confidence interval, 0.997–1.002; P =0.856) and adjusted Cox models (hazards ratio, 1.000; 95% confidence interval, 0.997–1.002; P =0.950). Next, we divided the entire cohort into 3 groups based on donor troponin I values: <1 ng/mL (n=7812), 1 to 10 ng/mL (n=2770), and >10 ng/mL (n=361). Using unadjusted and adjusted Cox models and Kaplan–Meier analysis, there was no significant difference in recipient mortality at 30 days, 1 year, 3 years, or 5 years between the 3 groups. Similarly, cardiac allograft vasculopathy up to 5 years and primary graft failure up to 30 days of follow-up post transplant did not differ between the 3 donor troponin groups. The median length of hospital stay post transplant was also similar across groups. Conclusions—: Elevated donor troponin I levels in the setting of preserved left ventricular ejection fraction were not associated with intermediate-term mortality, cardiac allograft vasculopathy, or primary graft failure rates in hearts accepted for transplantation. This finding could help expand the donor pool. Abstract : Supplemental Digital Content is available in the text.